Microbubble destruction with ultrasound augments neovascularisation by bone marrow cell transplantation in rat hind limb ischaemia. Issue 4 (1st July 2005) - Enomoto, S; Yoshiyama, M; Omura, T; Matsumoto, R; Kusuyama, T; Nishiya, D; Izumi, Y; Akioka, K; Iwao, H; Takeuchi, K; Yoshikawa, J
Abstract : Objective: To examine the effects of microbubble destruction with ultrasound (MB) combined with bone marrow derived mononuclear cell transplantation (BMT) into ischaemic tissues in rat hind limb ischaemia. Methods and results: Unilateral hind limb ischaemia was surgically induced in Lewis rats. At postoperative day 7, rats were randomly divided into three groups: a vehicle treated group, an ultrasound treated group, and an MB treated group. MB treatment increased vascular endothelial growth factor mRNA as assessed by real time polymerase chain reaction (3.0-fold, p < 0.05). At four weeks, the MB group had increases in laser Doppler blood flow index (LDBFI; 1.2-fold, p < 0.05), angiographically detectable collateral vessels (angiographic score: 1.4-fold, p < 0.01), and capillary to muscle fibre ratio (1.4-fold, p < 0.01) in ischaemic limbs compared with the vehicle treated group. No differences were seen between the vehicle and ultrasound treated groups. Secondly, rats were allocated to vehicle treatment, BMT (5 × 10 6 cells/rat), or a combination of MB and BMT (MB+BMT) at seven days after hind limb ischaemia. BMT treatment significantly increased LDBFI, angiographic score, and capillary to muscle fibre ratio compared with vehicle treatment. Interestingly, MB+BMT treatment produced significantly greater LDBFI (1.2-fold, p < 0.01), angiographic score (1.5-fold, p < 0.01), and capillary to muscle fibre ratio (1.5-fold, p < 0.05) than BMT treatment alone. Conclusions: MB may be a useful technique to enhance BMT induced neovascularisation.